Condicionantes institucionais à execuç\~ao do investimento em infraestrutura no Brasil: Estudo de caso sobre a implementaç\~ao da ferrovia Transnordestina - Raphael Amorim Machado (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– This paper describes the implementation process of the Transnordestina Railway, which has been built under the scope of the Institutional Constraints on Implementation of Investment in Infrastructure project in Brazil. It looks for answering questions as such: Which institutional factors conditioned the implementation pace of the Transnordestina Railway project? What are the institutional innovations that were used to start up the project? These questions organize up the text around a list of institutional analysis variables, which were detected during the research process. The railway construction is lagging from its initial completion date of 2010 and its implementation value rised up. The text points out that many problems have arisen during the stages of planning and execution of the project. One of the research fidings is that the lack of knowledge about the implementation difficulties extended the project completion deadline, such as increased its financial, social and environmental cost.
Keywords: H54; J68; O18; R42; 330; infrastructure; transports; railways